The latest spectral analysis on asteroids at NAO Rozhen. Issue Volume 15:Issue S350(2019) (April 2019) - Bebekovska, Elena Vchkova; Borisov, Galin; Donchev, Zahary; Apostolovska, Gordana
Abstract: By virtue of the physical, chemical and dynamical characteristics of asteroids, researchers gain insight into the formation and evolution of our Solar system. Since these objects do not undergo any changes, or the changes during the Solar system evolution are insignificant, we are certain they carry important information regarding the formation of our planetary system and its evolution. Knowing the spectral class of an asteroid is crucial for determining its chemical properties. In our work the spectral classification was done on several asteroids by comparing their spectra with laboratory spectra. We determined spectral types of the asteroids by the overall shapes of the spectra between 450 nm and 700 nm. Increasing the number of asteroids with known rotation period, shapes and spectra enriches the asteroid database of physical and dynamical characteristics of asteroid population.